Women’s Vulnerability in International Conflicts: Challenges to Life, Security, and Human Rights (Texas Journal of Multidisciplinary Studies, 2025)
Despite growing international recognition of the importance of gender-inclusive peacebuilding, women continue to experience disproportionate harm and systemic exclusion in contemporary armed conflicts. This article investigates the paradox between extensive normative frameworks—such as United Nations Security Council Resolution 1325 and the Convention on the Elimination of All Forms of Discrimination against Women—and the persistent marginalization of women in peace and security processes. It explores how modern conflicts exacerbate women’s vulnerability through militarization, environmental destruction, forced displacement, and the erosion of social and legal protections. At the same time, the study challenges dominant victim-centered narratives by highlighting women’s agency as peacebuilders, mediators, and contributors to post-conflict recovery. The article argues that the failure to meaningfully integrate women into conflict prevention and resolution mechanisms undermines both the effectiveness and sustainability of peace outcomes. Strengthening gender-sensitive governance and international cooperation is therefore essential for advancing durable peace, human security, and sustainable development.